Managing the Exploitation of Natural Assets: lessons for low income countries. - Collier, P; Venables, A (OxCarre, 2008)
This paper provides an analytic review of the upstream aspects of the exploitation of natural resources: the assignment of ownership rights, taxation, the discovery process, extraction, renewability, and clean-up. It sets these issues within the principal-agent framework. It proposes that the present common system whereby governments sell extraction rights prior to discovery through signature bonuses is likely to be socially costly, since the sale of rights occurs at a stage where irreducible risks generate a severe discount. It also proposes that the present common system whereby governments sell extraction rights by means of negotiated deals might disadvantage governments relative to more transparent and competitive systems such as auctions. While the paper is primarily analytic, it also briefly reviews African experience, suggesting that both high commodity prices and the low value of discovered assets per hectare imply major opportunities.